Effects of Vitamin D Supplementation on Serum 25-Hydroxy Cholecalciferol in Inflammatory Bowel Diseases: A Meta-Analysis of Randomized Clinical Trials - Reza Ramezani; Parivash Ghorbaninejad; Masoumeh Eslahi; Leila Sheikhi; Fatemeh Abbasi; Mohaddeseh Hasanzadeh; Saba Mohammadpour; Alireza Milajerdi (International Journal of Preventive Medicine)
Background: Earlier studies about the influence of vitamin D (Vit D) supplementation on patients with inflammatory bowel disease (IBD) reported inconsistent results. Current comprehensive systematic review and meta-analysis was conducted to assess the effect of Vit D supplementation on clinical and subclinical factors in patients with IBD. Methods: PubMed, Scopus, and Web of Science databases were searched for relevant randomized controlled trials (RCTs) on the effect of Vit D supplementation in IBD patients, published up to March 2023. Data were analyzed by the random-effect model. Heterogeneity was assessed by Cochran’s Q test and I-square (I2) statistic. The mean differences (MDs) were calculated as the summary effect size. Results: We included nine related articles, and our findings indicated that vitamin D administration increased serum vitamin D levels compared to placebo (weighted mean difference (WMD): 12.08; 95% confidence interval (95% CI): 9.06, 15.09; I2 = 97.01%; P < 0.001) in IBD patients. However, it had no significant influence on disease activity (standardized mean difference (SMD): 0.27; 95% CI: -0.42, 0.95; I2 = 91.7%; P < 0.001) or serum levels of C-reactive protein (CRP) (WMD: -1.42; 95% CI: -3.90, 1.06; I2 = 41.9%; P = 0.262). Conclusions: Current meta-analysis showed a significant effect of Vit D supplementation on increasing serum cholecalciferol. However, no significant effects of Vit D supplementation on the disease activity and serum levels of CRP were seen. Further studies are needed to expand current knowledge in this issue and found a significant increment in serum 25-hydroxy cholecalciferol concentrations following Vit D supplementation in IBD patients.